Using Polar Faculae to Determine the Sun’s High-latitude Rotation Rate. I. Techniques and Initial Measurements - Neil R. Sheeley Jr. (The Astrophysical Journal, 2024)
This paper describes a new way of determining the high-latitude solar rotation rate statistically from simultaneous observations of many polar faculae. In this experiment, I extracted frames from a movie made previously from flat-fielded images obtained in the 6767 Å continuum during 1997–1998 February and used those frames to construct spacetime maps from high-latitude slices of the favorably oriented south polar cap. These maps show an array of slanted tracks whose average slope indicates the east–west speed of faculae at that latitude, λ _s . When the slopes are measured and plotted as a function of latitude, they show relatively little scatter ∼ 0.01–02 km s ^−1 from a straight line whose zero-speed extension passes through the Sun’s south pole. This means that the speed, v ( λ _s ), and the latitudinal radius, ${R}_{\odot }\cos {λ }_{s}$ , approach 0 at the same rate, so that their ratio gives a nearly constant synodic rotation rate ∼8.°6 day ^−1 surrounding the Sun’s south pole. A few measurements of the unfavorably oriented north polar cap are consistent with these measurements near the south pole.